FACTORS CAUSING POVERTY AND MECHANISMS OF THEIR REDUCTION - Otavaliyev Bobirjon Sobirjon ugli (American Journals Publishing, 2023)
Today, it is necessary to deepen research on the factors causing poverty in our country and their causes. This article is based on the research status of the theory of the formation of poverty and tries to propose it together with practical experience. It is based on analytical guidelines that reveal the internal logical connections between the various factors that cause poverty. At the same time, the current state of research on the mechanism of poverty reduction is revealed.
Keywords: Poverty, economic changes, population welfare, social capital, rule of law, entrepreneurship, development, progress.